Hydroxamic acid - A novel molecule for anticancer therapy - Dilipkumar Pal; Supriyo Saha (Wolters Kluwer Medknow Publications, 2012)
Hydroxamic acid is a potent moiety not only in the field of cancer therapy but also as a mutagenic agent. Among the various derivatives of hydroxamic acid, SAHA (Suberoylanilide Hydroxamic Acid) is considered as a potent anticancer agent. Scientists from the different corner synthesized different hydroxamic acid moieties with some straight chain oxazole, thiadiazole, biphenyl moieties in the terminal position. Acetylation and deacetylation of histones of the core proteins of nucleosomes in chromatin play an important role in the regulation of gene expression. The level of acetylation of histones is established and maintained by two classes of enzymes, histone acetyltransferase and histone deacetylases, which have been identified as transcriptional coactivators and transcriptional corepressors, respectively. There is increasing evidence that aberrant histone acetylation has been linked to various malignant diseases. Great efforts are currently underway for the design of more potent and less toxic candidates for the treatment of cancer. In recent years, hydroxamic acid derivatives have attracted increasing attention for their potential as highly efficacious in combating various etiological factors associated with cancer. Our main intention to draw an attention is that this single functional moiety has not only fit in the receptor but also create a diversified activity.